لشركة في الفقه الإسلامي والوضعية المعاصرة - Ahmad Junaidi (Qawanin: Jurnal of Economic Syaria Law, 2017)
Many people believe that existing companies in the field of application are the product of Western civilization and are seen as evidence of their progress and this belief is wrong for many Islamic countries to convey them in bulk and to apply them without any scrutiny or development that is appropriate to the Islamic society. The company launches, among other things: 1) mixing of funds, 2) mixing of partners' business. The contract that creates this transaction is called because it is confused and this is the most used by the scholars. This research is concerned in highlighting companies in Islam, focusing on their own aspects, and indicating the most important differences between them and the developing companies